One‐Dimensional π–d Conjugated Coordination Polymer for Electrochromic Energy Storage Device with Exceptionally High Performance. Issue 20 (15th September 2020) - Cai, Guofa; Cui, Peng; Shi, Wenxiong; Morris, Samuel; Lou, Shi Nee; Chen, Jingwei; Ciou, Jing‐Hao; Paidi, Vinod K; Lee, Kug‐Seung; Li, Shuzhou; Lee, Pooi See
Abstract: The rational design of previously unidentified materials that could realize excellent electrochemical‐controlled optical and charge storage properties simultaneously, are especially desirable and useful for fabricating smart multifunctional devices. Here, a facile synthesis of a 1D π –d conjugated coordination polymer (Ni‐BTA) is reported, consisting of metal (Ni)‐containing nodes and organic linkers (1, 2, 4, 5‐benzenetetramine), which could be easily grown on various substrates via a scalable chemical bath deposition method. The resulting Ni‐BTA film exhibits superior performances for both electrochromic and energy storage functions, such as large optical modulation (61.3%), high coloration efficiency (223.6 cm 2 C −1 ), and high gravimetric capacity (168.1 mAh g −1 ). In particular, the Ni‐BTA film can maintain its electrochemical recharge‐ability and electrochromic properties even after 10 000 electrochemical cycles demonstrating excellent durability. Moreover, a smart energy storage indicator is demonstrated in which the energy storage states can be visually recognized in real time. The excellent electrochromic and charge storage performances of Ni‐BTA films present a great promise for Ni‐BTA nanowires to be used as practical electrode materials in various applications such as electrochromic devices, energy storage cells, and multifunctional smart windows. Abstract : A 1D π –d conjugated coordination polymer (CCP) is successfully fabricated in which specific organic linker and metal ions are selected with the aim of increasing the density of redox active centers and enabling conductive paths for charge transport. Moreover, this CCP enables dual electrochromic and energy storage functionalities in an integrated smart device.